Non-cytotoxic carbon nanocapsules synthesized via one-pot filling and end-closing of multi-walled carbon nanotubes. (January 2019) - Martincic, Markus; Vranic, Sandra; Pach, Elzbieta; Sandoval, Stefania; Ballesteros, Belén; Kostarelos, Kostas; Tobias, Gerard
Abstract: Filled carbon nanotubes (CNTs) find application in a variety of fields that expand from sensors to supercapacitors going through targeted therapies. Bulk filling of CNTs in general results in samples that contain a large amount of non-encapsulated material external to the CNTs. The presence of external material can dominate the properties of the resulting hybrids and can also induce side effects when employed in the biomedical field. Unless the encapsulated payloads have a strong interaction with the inner CNT walls, an additional step is required to block the ends of the CNTs thus allowing the selective removal of the non-encapsulated compounds while preserving the inner cargo. Herein we present a fast, easy and versatile approach that allows both filling (NaI, KI, BaI2, GdCl3 and SmCl3 ) and end-closing of multi-walled CNTs in a single-step, forming "carbon nanocapsules". Remarkably the encapsulation of GdCl3 and SmCl3 leads to the formation of tubular van der Waals heterostructures. The prepared nanocapsules are efficiently internalized by cells without inducing cytotoxicity, thus presenting a safe tool for the delivery of therapeutic and dianostic agents to cells. The synergies of novel carbon and inorganic hybrid materials can be explored using the present approach. Graphical abstract: Image 1